The changes in kynurenine metabolites induced by rTMS in treatment-resistant depression: A pilot study. (June 2021) - Tateishi, Hiroshi; Setoyama, Daiki; Kang, Dongchon; Matsushima, Jun; Kojima, Ryohei; Fujii, Yuka; Mawatari, Seiji; Kikuchi, Jun; Sakemura, Yuta; Fukuchi, Junko; Shiraishi, Takumi; Maekawa, Toshihiko; et al.
Abstract: Background: Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain stimulation technique that is considered a valuable and promising technique for improving depressive symptoms in treatment-resistant depression (TRD). However, the exact mechanism by which rTMS ameliorates depressive symptoms remains to be clarified. Objective: The aim of the present study was to analyzed the changes in metabolites of patients with TRD in the rTMS treatment, especially focusing on the kynurenine (KYN) pathway. Methods: Thirteen participants with TRD were enrolled in a high-frequency (10 Hz) rTMS study. Cognitive function, depressive symptoms and the concentration of plasma tryptophan (TRP) metabolites were measured at baseline and at the endpoint of rTMS treatment. Results: rTMS treatment significantly improved depressive symptom scores and some subscales of cognitive dysfunction. The present study has demonstrated that rTMS treatment significantly increased plasma TRP levels and significantly decreased plasma serotonin levels, while plasma KYN and kynurenic acid level as well as KYN/TRP ratio remained unchanged. Conclusions: This is the first metabolomic study of patients with TRD undergoing rTMS treatment. To validate the present results, it is necessary to increase the number of cases including controls, use a sample of cerebrospinal fluid, and measure blood concentration over time in the course of rTMS treatment.